Proximity-induced exponential amplification reaction triggered by proteins and small molecules. Issue 38 (14th April 2021) - Zhang, Yu-Peng; Wang, Hong-Peng; Dong, Ruo-Lan; Li, Si-Yao; Wang, Zhi-Gang; Liu, Shu-Lin; Pang, Dai-Wen
Abstract : A biosensor was designed based on proximity-induced exponential amplification reaction, which was suitable to detect proteins and small molecules. Abstract : We proposed a method to regulate nucleic acid polymerization by proximity and designed an ultrasensitive biosensor based on proximity-induced exponential amplification reaction for proximity assay of proteins (streptavidin) and small molecules (adenosine triphosphate), which allows us to detect a variety of interesting targets by simply changing the binding sites of DNA.